Humane [videorecording (Blu-Ray)] - Sparaga, Michael, 1973-; Baruchel, Jay, 1982-; Hampshire, Emily, 1981-; Gallagher, Peter, 1955- (Shudder, 2026)
In the wake of an environmental collapse that is forcing humanity to shed 20% of its population, a family dinner erupts into chaos when a father's plan to enlist in the government's new euthanasia program goes horribly awry.